Results of ‘varieties of ideas and happy days project’ for anger management in grade 2 secondary school students, Nareerat School, Phrae Province. - Thika, S.; Chandarasiri, P. (Chulalongkorn Medical Journal, 2023)
Background : Anger is natural emotion which is becoming an increasingly prevalent issue in children. This problem is becoming such a considerable predicament today, that has even become a concern among children as well. Therefore, it becomes very important to begin exploring this problem and ways that it can be dealt within the most effective manner to reduce inappropriate manifestations of and violent acts resulting from feelings of anger. Anger management has been report as an effectively adjunctive treatment for school-age children. Objective : To study anger management comparing control group and experimental group after had anger management program at Nareerat School, Phrae Province. Design : Experimental study. Setting : Nareerat School, Phrae Province. Materials and Methods : Twenty school-age children were recruited from Nareerat School Phrae Province from August 2012 until January 2013, The subjects were then randomized into experimental and control group. Each participant in the experimental group received the ten weeks of ‘Varieties of ideas and Happy - days Project’ intervention while the control subjects received standard program in the school. The instruments consisted of questionnaire for demographic assessment, anger management questionnaire and varieties of ideas and happy - days project for anger management. Descriptive statistic, non-parametric Wilcoxon signed ranks test and Analysis of Covariance; ANCOVA were used for the statistical analysis. Results : It was found that school children in the experimental group had statistically significantly increased anger management compared to the control group after anger management program. After 2 months, the experimental group had statistically significantly increased anger management. Conclusion : The results demonstrate that ‘varieties of ideas and happy - days project’ can reduce anger management in school-age children. This study could be used to plan for anger management and mental health promotion and prevention in adolescence.